ESTIMATION OF SOFTWARE SIZE USING FUNCTION POINT ANALYSIS ON INVENTORY INFORMATION SYSTEMS - Aser Anou; Imam Much Ibnu Subroto; Arief Marwanto (Universitas Islam Sultan Agung, 2022)
Indicators of good software development achievements are measured measurements on all aspects of software development, including the environment and systems of software. In this paper, indicators of the complexity of web-based software developed by the waterfall method with XML language-based entity database relations. This inventory information system functions as an integrated system with other systems in an integrated information system scope. Function point analysis (FPA) is used as a measuring device that can assess the complexity of components and functions of the software developed. The measurement results show that the overall value of the FPA is 180.83, which indicates that the application of inventory information systems is easy to use with low complexity. While the results of CFP and RCAF calculations also show that this application is quite simple so it is easy to use by various groups.